Epigenomic promoter alterations predict for benefit from immune checkpoint inhibition in metastatic gastric cancer. (8th January 2019) - Sundar, R; Huang, K K; Qamra, A; Kim, K -M; Kim, S T; Kang, W K; Tan, A L K; Lee, J; Tan, P
Abstract: Background: Utilization of alternative transcription start sites through alterations in epigenetic promoter regions causes reduced expression of immunogenic N-terminal peptides, which may facilitate immune evasion in early gastric cancer. We hypothesized that tumors with high alternate promoter utilization would be resistant to immune checkpoint inhibition in metastatic gastric cancer. Patients and methods: Two cohorts of patients with metastatic gastric cancer treated with immunotherapy were analyzed. The first cohort ( N = 24) included patients treated with either nivolumab or pembrolizumab. Alternate promoter utilization was measured using the NanoString ® (NanoString Technologies, Seattle, WA, USA) platform on archival tissue samples. The second cohort was a phase II clinical trial of patients uniformly treated with pembrolizumab ( N = 37). Fresh tumor biopsies were obtained, and transcriptomic analysis was carried out on RNAseq data. Alternate promoter utilization was correlated to T-cell cytolytic activity, objective response rate and survival. Results: In the first cohort 8 of 24 (33%) tumors were identified to have high alternate promoter utilization (APhigh ), and this was used to define the APhigh tertile of the second cohort (13 APhigh of 37). APhigh tumors exhibited decreased markers of T-cell cytolytic activity and lower response rates (8% versus 42%, P = 0.03). Median progression-free survival was lower in the APhigh group (55 versus 180 days, P = 0.0076). In multivariate analysis, alternative promoter utilization was an independent predictor of immunotherapy survival [hazard ratio 0.29, 95% confidence interval 0.099–0.85, P = 0.024). Analyzing tumoral evolution through paired pre-treatment and post-treatment biopsies, we observed consistent shifts in alternative promoter utilization rate associated with clinical response. Conclusion: A substantial proportion of metastatic gastric cancers utilize alternate promoters as a mechanism of immune evasion, and these tumors may be resistant to anti-PD1 immune checkpoint inhibition. Alternate promoter utilization is thus a potential mechanism of resistance to immune checkpoint inhibition, and a novel predictive biomarker for immunotherapy. Trial Registration: ClinicalTrials.gov Identifier: NCT#02589496